Disruption of DDX53 coding sequence has limited impact on iPSC-derived human NGN2 neurons - Muhammad Faheem; Eric Deneault; Roumiana Alexandrova; Deivid C. Rodrigues; Giovanna Pellecchia; Carole Shum; Mehdi Zarrei; Alina Piekna; Wei Wei; Jennifer L. Howe; Bhooma Thiruvahindrapuram; Sylvia Lamoureux; et al. (BMC, 2023)
Abstract Background The X-linked PTCHD1 locus is strongly associated with autism spectrum disorder (ASD). Males who carry chromosome microdeletions of PTCHD1 antisense long non-coding RNA (PTCHD1-AS)/DEAD-box helicase 53 (DDX53) have ASD, or a sub-clinical form called Broader Autism Phenotype. If the deletion extends beyond PTCHD1-AS/DDX53 to the next gene, PTCHD1, which is protein-coding, the individuals typically have ASD and intellectual disability (ID). Three male siblings with a 90 kb deletion that affects only PTCHD1-AS (and not including DDX53) have ASD. We performed a functional analysis of DDX53 to examine its role in NGN2 neurons. Methods We used the clustered regularly interspaced short palindromic repeats (CRISPR) gene editing strategy to knock out DDX53 protein by inserting 3 termination codons (3TCs) into two different induced pluripotent stem cell (iPSC) lines. DDX53 CRISPR-edited iPSCs were differentiated into cortical excitatory neurons by Neurogenin 2 (NGN-2) directed differentiation. The functional differences of DDX53-3TC neurons compared to isogenic control neurons with molecular and electrophysiological approaches were assessed. Results Isogenic iPSC-derived control neurons exhibited low levels of DDX53 transcripts. Transcriptional analysis revealed the generation of excitatory cortical neurons and DDX53 protein was not detected in iPSC-derived control neurons by western blot. Control lines and DDX53-3TC neurons were active in the multi-electrode array, but no overt electrophysiological phenotype in either isogenic line was observed. Conclusion DDX53-3TC mutation does not alter NGN2 neuronal function in these experiments, suggesting that synaptic deficits causing ASD are unlikely in this cell type.